Seasonality fingerprint on global trading of food-commodities - Quaini, Stefania,Saccani, Sebastiano,Vergalli, Sergio,Assom, Luigi,Beria, Marco,Codello, Alessandro,Monaco, Maurizio,Sabatini, Riccardo (Fondazione Eni Enrico Mattei, 2020)
We analyze the United Nations commodities trade database (UN comtrade), comprised of international commodities exchanges in volume and price with monthly resolution. We introduce a trade impact index to quantify the impact, in terms of distance travelled, of importing a specific food raw commodity in a specific period of the year and in a specific country of the world. This index captures the seasonal exchange of raw commodities in an insightful and concise manner.
10419/228791
Keywords: Graue Literatur; Trade; Food Commodities; Resource Access and Availability; Index; Fingerprint; Data Mining